2018
DOI: 10.1155/2018/9807139
|View full text |Cite
|
Sign up to set email alerts
|

Alda-1 Ameliorates Liver Ischemia-Reperfusion Injury by Activating Aldehyde Dehydrogenase 2 and Enhancing Autophagy in Mice

Abstract: Aldehyde dehydrogenase 2 (ALDH2) is a key enzyme for metabolism of reactive aldehydes, but its role during liver ischemia-reperfusion injury (IRI) remains unclear. In the present study, we investigated the effects of the ALDH2 activator, Alda-1, in liver IRI and elucidated the underlying mechanisms. Mice were pretreated with Alda-1 and subjected to a 90 min hepatic 70% ischemia model, and liver tissues or serum samples were collected at indicated time points after reperfusion. We demonstrated that Alda-1 pretr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…For example, several groups have demonstrated a protective role of autophagy during hepatic ischemia/reperfusion injury [[53], [54], [55]]. Moreover, a recent study also demonstrated that Alda-1 enhanced autophagy in a model of hepatic ischemia/reperfusion injury by increasing LC3II and p62 degradation [56]. In line with these results, here we found that Alda-1 significantly decreased p62 protein expression in the HFD + VC group (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…For example, several groups have demonstrated a protective role of autophagy during hepatic ischemia/reperfusion injury [[53], [54], [55]]. Moreover, a recent study also demonstrated that Alda-1 enhanced autophagy in a model of hepatic ischemia/reperfusion injury by increasing LC3II and p62 degradation [56]. In line with these results, here we found that Alda-1 significantly decreased p62 protein expression in the HFD + VC group (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Aldehyde dehydrogenase-2 (ALDH2), a liver mitochondrial enzyme that was initially implicated in the liver alcohol metabolism, has been associated with the pathophysiology of ischemia–reperfusion injury in several organs, including the liver [ 22 , 23 , 24 ]. Several authors reported that the use of Alda-1 (an activator of ALDH2) protects against liver ischemia–reperfusion injury (IRI) in the rat [ 25 , 26 ], but currently, no evidence exists on the direct PEG35 effect as a regulator of mitochondrial ALDH2 in cold old ischemic preservation strategies, although its cytoprotective action was indirectly evidenced when different organ preservation solutions were used for cold storage of fatty liver grafts [ 23 , 24 ]. ALDH2 could play a constitutive housekeeping role essential for the development and regulation of recycling and survival processes as those occurring in cold ischemia preservation [ 22 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact role of autophagy in I/R injury is still under debate, we and other groups have demonstrated that autophagy plays a positive role in protecting I/R injury. 37 , 44 , 45 , 46 , 47 In this study, we showed that elevated autophagy levels are required for the protective effect in Dj-1 deficiency hepatocytes, because inhibition of autophagy by 3-MA and CQ counteracted the hepatoprotective function of Dj-1 deficiency during hepatic I/R injury. Interestingly, like PINK1 and PARKIN, which are frequently mutated in many cases of early-onset familial PD, some DJ-1 mutations also lead to early-onset PD.…”
Section: Discussionmentioning
confidence: 66%